Gender differences in hematotoxicity of benzene-exposed workers, three cross-sectional studies on 218,061 subjects - Wang, Boshen; Han, Lei; Wang, Kun; Zhou, Yanhua; Pu, Yuepu; Zhang, Juan; Zhu, Baoli (Environmental science and pollution research international, 2021)
Our aim was to analyze the effects of benzene exposure on hematotoxicity in workers, with a focus on gender differences. The study was divided into three parts, and the survey included 218,061 workers. Since 2017, some workers are selected from the total workers each year to explore the possible influencing factors (age, duration of benzene exposure, TWA (8-h time-weighted average) of benzene, SPMA (S-phenylmercapturic acid), MDA (malondialdehyde), 8-OHdG (8-hydroxy-2′-deoxyguanosine) of different hematotoxicity of different genders). The abnormal rate of WBC (white blood cell), ANC (absolute neutrophil count), and platelets of female workers in the benzene exposure group was higher than that of males in the benzene exposure group and also higher than that of the female workers in the control group. Research results in 2019 showed increased SPMA as well as increases their DNA damage including 8-OHdG and MDA in benzene-exposed female workers compared to those in the control female group (all p < 0.05. SPMA, 8-OHdG, and MDA in benzene exposure female workers increased 555%, 183%, and 33.3%, respectively). Female workers are at significantly higher risk for blood system effects of benzene exposure. Therefore, more stringent standards and guidelines may be needed to protect the changing professional population, especially for females.